Coating of ß-tricalcium phosphate scaffolds—a comparison between graphene oxide and poly-lactic-co-glycolic acid. (4th August 2015) - Ardjomandi, N; Henrich, A; Huth, J; Klein, C; Schweizer, E; Scheideler, L; Rupp, F; Reinert, S; Alexander, D
Abstract: Bone regeneration in critical size defects is a major challenge in oral and maxillofacial surgery, and the gold standard for bone reconstruction still requires the use of autologous tissue. To overcome the need for a second intervention and to minimize morbidity, the development of new biomaterials with osteoinductive features is the focus of current research. As a scaffolding material, ß-tricalcium phosphate (ß-TCP) is suitable for bone regeneration purposes, although it does not carry any functional groups for the covalent immobilization of molecules. The aim of the present study was to establish effective coating variants for ß-TCP constructs to enable the biofunctionalization of anorganic blocks with different osteogenic molecules in future studies. We established working protocols for thin surface coatings consisting of polylactic-co-glycolic acid (PLGA) and graphene oxide (GO) by varying parameters. Surface properties such as the angularity and topography of the developed scaffolds were analyzed. To examine biological functionality, the adhesion and proliferation behavior of jaw periosteal cells (JPCs) were tested on the coated constructs. Our results suggest that PLGA is the superior material for surface coating of ß-TCP matrices, leading to higher JPC proliferation rates and providing a more suitable basis for further biofunctionalization in the field of bone tissue engineering.